Kiprah Pesantren: Solusi Konflik Sosial dan Etika Bangsa yang Multikultur - Dwi Mariyono; Masykuri Masykuri (Journal on Education, 2023)
This study uses a qualitative approach with an analytical descriptive method with a type of literature review. Data related to educational issues, pesantren problems, social conflicts, national ethics and maps of Indonesian Bangwa that Multicultural Researchers have gathered to be studied and examined using the theory of Interactive Huberman and Saldana (2014). Data are collected, selected, displayed, condensed for marked and interpreted and concluded in a comprehensive explanation. The findings of this study have shown a real concept map that Islamic Islamic Islamic education education has actually given a response to multicultural social conflicts and ethics as a development of noble ideals of muffling and merges social and ethical disputes about tradition in all sectors of society. Revitalization of the process as a resolution of the transformation of Islamic values that are full of multiculture by prioritizing elements. First, changes in approach to functional understanding of religion. Integrating religious nuances into life, including changing, interpreting, and renewing religious values in response to social development and problems. Second, understanding of pluralism and diversity in high national ideals. In this understanding the accommodative attitude of its adherents towards religion is consciously implanted the importance of increasing and honing intellectuals, and the importance of peace and togetherness to remain side by side by side without conflict that lead to divisions and civil war. Thus, the values of Islamic education that are on an ontology are very clear the truth can be a magnet to be interesting into a friendly and peaceful process of social interaction if it rests on the true principles of Islam.